1987
DOI: 10.1111/j.1528-1157.1987.tb03690.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Estrogen, Progesterone, and Ionized Calcium on Seizures During the Menstrual Cycle of Epileptic Women

Abstract: Previous research suggested a positive relationship between levels of serum estrogen and seizures, a negative relationship between levels of serum Ca++ and seizures, and a negative relationship between serum levels of estrogen and Ca++. This study sought a relationship between levels of serum estrogen, ionized calcium, progesterone, and its possible effect on seizures during the menstrual cycle of epileptic women. The negative relationship between serum estrogen and Ca++ was confirmed. However, a study of 15 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0
1

Year Published

1988
1988
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 29 publications
3
28
0
1
Order By: Relevance
“…In other studies, estrogen applied topically created new seizure foci and activated previously present cortical epileptogenic foci (24), and on a neuronal level, estrogens enhance glutamate excitation (25). Some questions remain regarding the significance of this estrogen seizure-provoking effect in humans because studies involving catamenial epilepsy have not consistently confirmed that high levels of estrogen are responsible for exacerbation of seizures (1,22,26,27). Nonetheless, the concept that estrogen may lower the seizure threshold in some individuals is reasonably well accepted.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, estrogen applied topically created new seizure foci and activated previously present cortical epileptogenic foci (24), and on a neuronal level, estrogens enhance glutamate excitation (25). Some questions remain regarding the significance of this estrogen seizure-provoking effect in humans because studies involving catamenial epilepsy have not consistently confirmed that high levels of estrogen are responsible for exacerbation of seizures (1,22,26,27). Nonetheless, the concept that estrogen may lower the seizure threshold in some individuals is reasonably well accepted.…”
Section: Discussionmentioning
confidence: 99%
“…There is a positive correlation between levels of P associated with the follicular phase of the menstrual cycle and increased seizure threshold (Backstrom, 1976). Women suffering from catamenial epilepsy display more dense and intense clusters of seizures during the follicular phase of the menstrual cycle, just after circulating levels of P have decreased drastically (Backstrom, 1976;Duncan, Read, & Brodie, 1993;Jacono & Robertson, 1987;Rosciszewska, Buntner, Guz, & Zawisza, 1986;Zimmerberg & Morrow, 1996). Progesterone levels are also reduced in catamenial epilepsy patients compared to normal and epileptic patients (Bonuccelli, et al, 1989;Narbone et al, 1989), and intermittent P therapy can decrease the frequency of complex partial seizures in women with epilepsy (Chia & Scarffe, 1993;Herzog, 1986).…”
mentioning
confidence: 96%
“…There is a correlation between concentrations of P associated with the follicular phase of the menstrual cycle and increased seizure threshold [4]. Women suffering from catamenial epilepsy display more dense and intense clusters of seizures during the follicular phase of the menstrual cycle, just after circulating levels of P have decreased drastically [4, 5, 6, 7, 8]. P levels are also reduced in catamenial epilepsy patients compared to normal patients and epileptic patients [9, 10], and intermittent P therapy can decrease the frequency of complex partial seizures in women with epilepsy [11, 12].…”
Section: Introductionmentioning
confidence: 99%